APLIKASI VISUALISASI MATERI PEMBELAJARAN KIMIA DAN BIOLOGI BERBASIS WEB - Anita Octasia; Dwiza Riana (Paradigma, 2009)
Limitations and difficulties of teachers in delivering materials to make software in educational environments haveincreased, especially at the senior high school level. That's what makes the writer develops software learning thataims to assist teachers in presenting materials. The materials can help students more easily understand the lessonsin school, especially for a chemistry and biology subjects in senior high school. Research methods used in thewriting of this research is the analysis of the program. First, the authors analyze the previous program, learn thereference related to the study. They collect the data from books, literature and also from internet browsing. Next,they improve the program by creating new program and proposed in web base aplication. Visualisation andpresenting the developed applications uses software such as Adobe Flash CS3 and Macromedia Dreamweaver 8 sothat they can create visualized applications of learning materials for biology and chemistry at the high schoollevel. The proposed program is expected to help the teachers in solving the problem of delivering materials.KeywordsBiologi, Berbasis Web,Kimia, Materi Pembelajaran